Environmental history of the northwestern Québec Treeline. (15th February 2019) - Gajewski, K.
Abstract: Latitudinal treeline in northwestern Québec, Canada, is a broad band of forest-tundra between 56 and 58°N. Three new pollen records from the forest-tundra zone were combined with ten previously-published records to form a transect of paleoecological data across this treeline. The area was deglaciated ∼6–7 ka, with only a brief period of shrub tundra vegetation in the oldest sediments of all sites. Noticeable values of Populus, Juniperus and Larix pollen percentages were found during this time in the southernmost sites, suggesting they comprised part of the initial plant migration. Maximum Picea pollen percentages were found between 2 and 4 ka across the boreal forest and forest-tundra, with values remaining constant in the boreal forest and decreasing in the forest-tundra in the past 3 ka. Across the entire area, pollen influx decreased in the past 4 ka, and non-arboreal pollen increased in the forest-tundra, suggesting an opening of the forest and decrease in terrestrial production. Charcoal influx also declined, indicating a reduction in fire activity in the past 2–4 ka. Although the treeline has remained in the same average location in the region over the past 6 ka, the strength of the temperature gradient across the frontal zone changed over the course of the Holocene. Highlights: Rapid migration of trees after deglaciation. Maximum temperatures 5-3ka. Neoglacial cooling shown by pollen percentages, pollen and charcoal influx. Climate gradient across treeline changed through time.